Suffering in the doctor-patient relationship: Medicine as the science of suffering - Brera, Giuseppe R. (Medicina e Morale, 1987)
In medical science today, much attention is paid not only to what can be experimental, reproducible, observable or describable in data, but also to what concerns the subjectivity of the physician and the patient. We thus break away from a positivistic conception that does little to illuminate our path in this order of phenomena to enter with an observation that wants to be phenomenological into what seems to best characterise the meaning of Medicine and that from bio-science reveals it to us as anthropo-science, a science of man-for-man.